Direct Repression of FLIP Expression by c-myc Is a Major Determinant of TRAIL Sensitivity - M. Ricci; Zhaoyu Jin; Michael Dews; Duonan Yu; Andrei Thomas‐Tikhonenko; David T. Dicker; Wafik S. El‐Deiry (2004)
Tumor necrosis factor alpha (TNF-alpha)-related apoptosis-inducing ligand (TRAIL) is a member of the TNF-alpha family of death receptor ligands and holds great therapeutic potential as a tumor cell-specific cytotoxic agent. Using a panel of established tumor cell lines and normal cells, we found a significant difference between the number of TRAIL-sensitive cells expressing high levels of c-myc and TRAIL-resistant cells expressing low levels of c-myc (P < 0.05, n = 19). We also found a direct linear correlation between c-myc levels and TRAIL sensitivity in TRAIL-sensitive cell lines (r = 0.94, n = 6). Overexpression of c-myc or activation of a myc-estrogen receptor (ER) fusion sensitized TRAIL-resistant cells to TRAIL. Conversely, small interfering RNA (siRNA)-mediated knockdown of c-myc significantly reduced both c-myc expression and TRAIL-induced apoptosis. The gene encoding the inhibitor of caspase activation, FLICE inhibitory protein (FLIP), appears to be a direct target of c-myc-mediated transcriptional repression. Overexpression of c-myc or activation of myc-estrogen receptor (ER) decreased FLIP levels both in cell culture and in mouse models of c-myc-induced tumorigenesis, while knocking down c-myc using siRNA increased FLIP expression. Chromatin immunoprecipitation and luciferase reporter analyses showed that c-myc binds and represses the human FLIP promoter. c-myc expression enhanced TRAIL-induced caspase 8 cleavage and FLIP cleavage at the death-inducing signaling complex. Combined siRNA-mediated knockdown of FLIP and c-myc resensitized cells to TRAIL. Therefore, c-myc down-regulation of FLIP expression provides a universal mechanism to explain the ability of c-myc to sensitize cells to death receptor stimuli. In addition, identification of c-myc as a major determinant of TRAIL sensitivity provides a potentially important screening tool for identification of TRAIL-sensitive tumors.